Spirituality, infertility‐related stress, and quality of life in Brazilian infertile couples: Analysis using the actor‐partner interdependence mediation model. Issue 2 (5th February 2018) - Casu, Giulia; Ulivi, Giulia; Zaia, Victor; Fernandes Martins, Maria do Carmo; Parente Barbosa, Caio; Gremigni, Paola
ABSTRACT: Infertility has a stressful impact on both partners, with adverse effects on the quality of life of infertile couples. Spirituality is a meaning‐based strategy that can protect couples against infertility's negative impact on quality of life, but analysis of this mediator relationship in infertile couples has not been reported. We adopted a dyadic approach and used the actor‐partner interdependence mediation model to examine whether and how women's and men's spirituality was associated with their own and their partners' infertility‐related stress and quality of life. In 2014, 152 infertile couples starting their first fertility treatment at a private clinic in Brazil were recruited and completed self‐reports of spirituality, infertility‐related stress, and quality of life. Results indicated that women's and men's level of spirituality was positively associated with their own quality of life directly and indirectly, by reducing their own infertility‐related stress. Their spirituality was associated with an increase in their partners' quality of life only indirectly, by reducing their partners' infertility‐related stress. Findings highlight the importance of assessing and promoting spirituality as a coping resource that infertile women and men might use to deal with the stress of infertility and reduce its adverse effects on quality of life.